Estimating the Cost of Spinopelvic Complications After Adult Spinal Deformity Surgery - Zuckerman SL; Cher D; Capobianco R; Sciubba D; Polly DW (Dove Medical Press, 2023)
Scott L Zuckerman,1 Daniel Cher,2 Robyn Capobianco,2 Daniel Sciubba,3 David W Polly4 1Department of Neurological Surgery, Vanderbilt University Medical Center, Nashville, TN, USA; 2SI-BONE, Inc, Santa Clara, CA, USA; 3Department of Neurosurgery, Zucker School of Medicine at Hofstra, Long Island Jewish Medical Center and North Shore University Hospital, Northwell Health, Manhasset, NY, USA; 4Department of Orthopaedic Surgery, University of Minnesota, Minneapolis, MN, USACorrespondence: Scott L Zuckerman, Department of Neurological Surgery, Vanderbilt University Medical Center, Nashville, TN, USA, Email scott.zuckerman@vumc.orgObjective: Reoperations for spinopelvic failure after adult spinal deformity (ASD) surgery are common. We sought to determine the added costs of ASD surgery attributable to reoperations for spinopelvic construct failures.Methods: We constructed a Markov process model to calculate the expected discounted 5-year costs of spinopelvic construct failures after ASD surgery. The Nationwide Inpatient Sample (NIS) was queried to estimate the number of ASD surgeries. Model inputs were based on literature review and expert opinion. ASD surgery was defined as thoracolumbar fusion of 4 or more levels with pelvic fixation. The following pelvic fixation failures were included: 1) rod fracture or pseudarthrosis from L4-S1, 2) iliac screw failure or set plug dislodgment, 3) iliac screw prominence, and 4) sacroiliac (SI) joint pain. The number of patients undergoing ASD surgery annually in the US was determined using a commercial claims database.Results: The net present value 5-year cost per patient for spinopelvic complications was $35,265, equal to 29% of index surgery costs. Given an estimated 27,580 cases annually in the US, the additional cost to address spinopelvic complications reach nearly $1 billion over 5-years. A sensitivity analysis showed that these costs were most sensitive to the rate of rod fracture/pseudarthrosis, iliac screw prominence, and reoperation.Conclusion: A conservative estimate of the cost of spinopelvic failures after ASD surgery is substantial, nearly $1 billion over 5-years. We propose a method of capturing spinopelvic fixation failures for use in future clinical studies and cost analyses.Keywords: spinopelvic, sacroiliac, deformity surgery